In the aftermath of catastrophe : founding Judaism, 70 to 640 - Neusner, Jacob, 1932-2016 (McGill-Queen's studies in the history of religion., 2009)
Neusner argues that the Judaism that emerged in late antiquity experimented with solutions to a critical and enduring issue of culture that continues to engage humanity - the crisis provoked by calamity. Exemplified in our time by the German war against the Jews from 1933-1945, in antiquity calamity took the form of the destruction in 70 C.E. of the Temple of Jerusalem and the cessation of its sacrifices, putting an end to the cultic calendar by which people had measured the passage of time in the heavens and maintained their relationship with God on earth. Resolution of this crisis required a radical solution, the reversion to prophecy, which had as a consequence restoration of world order Judaism as we know it responded then and continues to respond now to the paramount problem of that day and ours - the end of the old order and the advent of the new.